Increased Burden of Vision Impairment and Eye Diseases in Persons with Chronic Kidney Disease — A Population-Based Study - Wong, Chee Wai (EBioMedicine, 2016)
BACKGROUND: Chronic kidney disease (CKD) has been shown to be associated with diabetic retinopathy (DR) and age-related macular degeneration (AMD), leading causes of blindness in elderly adults in previous studies. However, the association of CKD with visual impairment (VI) is not clear. We aimed to examine the association of CKD with VI and other age-related ocular diseases in a population-based sample of Asian adults. METHODS: We analyzed data from 10,033 adults aged 40–80 years who participated in the Singapore Epidemiology of Eye Diseases (SEED, 2004–11) Study. CKD was defined as an estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73 m(2) from serum creatinine. VI was defined as best-corrected visual acuity < 20/40 in the better eye. Cataract, retinopathy, DR, glaucoma and AMD were assessed using standardized ocular examination, retinal photography and visual field assessments. The associations of CKD with VI and ocular conditions were examined using logistic regression models adjusted for age, sex, race, smoking, alcohol intake, education status, body mass index, systolic blood pressure, diabetes mellitus, cholesterol levels and cardiovascular disease. FINDINGS: The prevalence of VI and ocular disease were significantly higher in participants with CKD (36.1% and 84.7%) than in those without (12.9% and 54.3%, both p < 0.001). In multivariable models, CKD was significantly associated with VI (odds ratio [95% confidence interval] = 1.34 [1.14–1.58]), any ocular disease (1.28 [1.03–1.61]), cataract (1.24 [1.01–1.52]), any retinopathy (1.77 [1.45–2.15]), and DR (1.94 [1.47–2.54]). INTERPRETATION: The burden of VI and eye diseases is high among persons with CKD. Our findings suggest that it may be useful to screen for ocular disease and VI in persons with CKD.